NEMIPTERUS DELAGOAE SMITH (NEMIPTERIDAE: PISCES) A NEW RECORD FROM THE INDIAN SEAS - Rajagopalan, M; Karuppaswamy, P; Regunathan, A (Indian Journal of Fisheries, 2011)
The occurrence of Nemipterus delagoae Smith is reported here for the firsttiii» from the Indian seas based on one specimen 231 mm total length, collectedfrom 40-m depth at 9°35'N 76°05'E along the southwest coast of India, The speciesis described and illustrated